Factors spurring Green Building Index consultancy acceptance - Mat Raschid, Mohd Yazah; Sharif, Roslina; Thahir, M. M.; Ismail, Abdul Halim (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2016)
The purpose of this paper is to investigate the factors influencing Green Building Index consultancy (GBI) acceptance in “green” residential buildings in Malaysia. A survey questionnaire instrument was utilized to gather data opinion of 150 respondents of building construction consultants and developers with local building authorities involving planners, architects and green building senior officers. Based on the quantitative analysis and results, the discussion about the study variables is revealed with ANOVA and correlational analysis. The study reveals that overall perception of cost effectiveness among specializations were significantly different while, the correlational analysis shows that there is significant relationship between management, quality of design, time effectiveness, quality of result, compliance with GBI requirement and cost effectiveness. This paper provides insights into the green building issues and contributes to the understanding of the consultancy in green residential building development.